CALCULATION AND EXPERIMENTAL RESEARCHES OF PROCESS COOLING OF BARS IN UNHEATED THERMOSTATS - Kayukov , Yuri; Nazarenko , Irene; Kuzmenko , Alla; Chizhov , Sergey (Scientific Journal "Metallurgy", 2020)
Calculation and experimental researches of cooling process for steel bars in the unheated thermostats after an exit from crystallizators of furnaces of ESR are executed. The rational temperature and times modes of cooling of bars which allow to promote the carrying capacity of these aggregates at unchanging quality of metal are offered. As practice of exploitation of thermostats shows, finishing period of cooling of bars of ESR is characterized by subzero intensity of taking of warmth from the superficial layers of metal which is accompanied by the substantial increase of duration of its stay in the swept volume of asms, and, consequently, and by the decline of their carrying capacity. Complex experimentally-theoretical approach to the mentioned problem is included implementation of series of experiments in relation to a study and analysis of distribution of temperature on the cut of bars of ESR on the different stages of their cooling, mathematical design of such process and calculation part in relation to determination of its rational temperature parameters. Experiments in relation to a study pour temperatures in the bars of ESR carried out during their transporting from crystallizers of furnaces of ESR to the unheated thermostat and further cooling in its swept volume. Studied kinetics of cooling of control bars which place in the different areas of the swept volume of the unheated thermostat by taking temperature of superficial and internal layers of metal. The hot ends of sensors of the flexible screened термокабеля placed in four points (on an axis and in the center of surface of overhead and lateral verges) in three (left butt-end, middle and right butt-end) crossrunners of bars. Distribution of temperature in the cooled bars was determined by the decision of three-dimensional nonlinear differential equation of heat-conducting. Equation of heat-conducting with regional terms presented in a finite-difference kind and decided numeral methods. Value of coefficient of heat emission it was calculated a convection after the known dependences taking into account maximal intensity of taking of warmth on the initial stage of cooling of metal. Results got on computer, high-quality comport with experimental data about temperature of central and superficial layers of bars, located in the different areas of the swept volume of